Artificial intelligence enables whole-body positron emission tomography scans with minimal radiation exposure. - Wang, Yan-Ran (Joyce); Baratto, Lucia; Hawk, K. Elizabeth; Theruvath, Ashok J.; Pribnow, Allison; Thakor, Avnesh S.; Gatidis, Sergios; Lu, Rong; Gummidipundi, Santosh E.; Garcia-Diaz, Jordi; Rubin, Daniel; Daldrup-Link, Heike E. (European Journal of Nuclear Medicine & Molecular Imaging, 2021)
Purpose: To generate diagnostic 18F-FDG PET images of pediatric cancer patients from ultra-low-dose 18F-FDG PET input images, using a novel artificial intelligence (AI) algorithm. Methods: We used whole-body 18F-FDG-PET/MRI scans of 33 children and young adults with lymphoma (3–30 years) to develop a convolutional neural network (CNN), which combines inputs from simulated 6.25% ultra-low-dose 18F-FDG PET scans and simultaneously acquired MRI scans to produce a standard-dose 18F-FDG PET scan. The image quality of ultra-low-dose PET scans, AI-augmented PET scans, and clinical standard PET scans was evaluated by traditional metrics in computer vision and by expert radiologists and nuclear medicine physicians, using Wilcoxon signed-rank tests and weighted kappa statistics. Results: The peak signal-to-noise ratio and structural similarity index were significantly higher, and the normalized root-mean-square error was significantly lower on the AI-reconstructed PET images compared to simulated 6.25% dose images (p < 0.001). Compared to the ground-truth standard-dose PET, SUVmax values of tumors and reference tissues were significantly higher on the simulated 6.25% ultra-low-dose PET scans as a result of image noise. After the CNN augmentation, the SUVmax values were recovered to values similar to the standard-dose PET. Quantitative measures of the readers' diagnostic confidence demonstrated significantly higher agreement between standard clinical scans and AI-reconstructed PET scans (kappa = 0.942) than 6.25% dose scans (kappa = 0.650). Conclusions: Our CNN model could generate simulated clinical standard 18F-FDG PET images from ultra-low-dose inputs, while maintaining clinically relevant information in terms of diagnostic accuracy and quantitative SUV measurements.